2014
DOI: 10.1016/j.system.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding language teachers' practice with educational technology: A case from China

Abstract: This article explores how eight secondary school teachers integrated educational technology into English language teaching in Beijing, China and considers their views of the factors influencing technology use. Analysing data from classroom recordings and follow-up interviews, this study revealed that PowerPoint was the most frequently used technological application in the classroom, while the internet and other technological tools were also used by the teachers. They employed educational technology for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…Teachers all over the world are encouraged to integrate technology in their teaching and, at the same time, face many challenges in using technology. These challenges vary from external factors, such as technology availability and workload (Yang and Huang 2008), teachers' pedagogical beliefs (Li 2008), to technology competence and confidence (Lam 2000;Li 2014;Thao 2003). It is therefore important to realise that attention should be given to the ways in which technologies can be used to attain teaching and learning objectives, rather than to which technologies can (or should) be used (Li 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers all over the world are encouraged to integrate technology in their teaching and, at the same time, face many challenges in using technology. These challenges vary from external factors, such as technology availability and workload (Yang and Huang 2008), teachers' pedagogical beliefs (Li 2008), to technology competence and confidence (Lam 2000;Li 2014;Thao 2003). It is therefore important to realise that attention should be given to the ways in which technologies can be used to attain teaching and learning objectives, rather than to which technologies can (or should) be used (Li 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These challenges vary from external factors, such as technology availability and workload (Yang and Huang 2008), teachers' pedagogical beliefs (Li 2008), to technology competence and confidence (Lam 2000;Li 2014;Thao 2003). It is therefore important to realise that attention should be given to the ways in which technologies can be used to attain teaching and learning objectives, rather than to which technologies can (or should) be used (Li 2014). To facilitate this, teachers need to engage in critical reflection, in which they assess the extent to which the use of a particular technology facilitates or hinders attainment of a particular learning objective.…”
Section: Resultsmentioning
confidence: 99%
“…Technological competence and confidence are among the frequently mentioned reasons for teachers' adopting or rejecting technology in their teaching practices. If teachers do not believe they are competent and confident in technology, there is a high chance that they will be reluctant to use it (Li, 2014). Teachers' negative self-perceptions about their confidence in technology form a barrier for their integration of it into their teaching (Becta, 2004).…”
Section: Teacher's Use Of Technologymentioning
confidence: 99%
“…It is indicated that teachers may be reluctant to use technology if their efforts are not appreciated by school administrators (Hutchison & Reinking, 2010). Additionally, in some educational contexts, teaching is exam-oriented and textbooks are the main input sources; in such settings technology integration is not shown to be successful (Li, 2014).…”
Section: Teacher's Use Of Technologymentioning
confidence: 99%
See 1 more Smart Citation